Pengaruh Aplikasi Kalsium terhadap Getah Kuning pada Buah Manggis (Garcinia mangostana L.) - Indah Wulandari; Roedhy Poerwanto (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2010)
ABSTRACTThis experiment was conducted to study the effect of calcium applicatian on gamboge in mangosteen fruit. Calcium materials used in this research was dolomite. This research was conducted from November 2007 to April 2008 at mangosteen orchard, Karacak, Leuwiliang, Bogor. The treatment design was Randomized Completely Block Design with three replications. The experiment consist of one factor, i.e. dosages of calcium (0, 2.5, 3.0 and 3.5 ton Ca2+/ ha). The result showed that dolomite application with dosage of 3.5 ton Ca2+/ha reduced gamboge in mangosteen rind significantly than control (0 ton Ca2+ha- 1) but no significant effect on gamboge in mangosteen aryl.Key words: dolomite, dosages, rind, and aryl